Avaliação do desempenho de vida útil do biocoagulante de moringa liofilizado - Santos, Bruna Souza dos (2019)
The use of Moringa oleifera (MO) seeds has been the subject of studies to treat water and effluents due to their biocoagulant potential. However, one of the factors that makes the use of seed extract in industrial scale unfeasible is its short shelf-life after processing. In view of the problem, the present study aimed to produce the biocoagulant of MO for pre-treatment by the drying process via lyophilization, and to evaluate its coagulant potential in a longer period of storage. For the study, optimization of the biocoagulant preparation conditions was performed using a Rotational Central Compound Design (RCCD), analyzing the effects of the MO mass and the time of extraction of the coagulant protein in ultrasound. Coagulation / flocculation / sedimentation experiments were carried out using the biocoagulant to remove the color of synthetic wastewater produced with the commercial blue dye 5G. A statistically validated mathematical model was obtained for the variable-response color removal. The optimum conditions obtained for color removal were a concentration of MO from 2.38 g to 100 mL of distilled water and 4 minutes for the sedimentation time. Under these conditions the removal of the color parameter was 22.41% when produced in aqueous medium. It was also evaluated the effect of the concentration of sodium chloride (NaCl) and potassium chloride (KCl) solutions in the process of extraction of the biocoagulant applying a completely randomized design (CRD), aiming at the best extraction condition and consequent improvement in color removal. The highest percentage of color removal of the synthetic waste water evaluated was 28.41%, obtained by saline KCl 1 mol L-1. From the best conditions obtained with the optimization and with the defined solution, the biocoagulant of lyophilized MO was prepared. The characterization of lyophilized aqueous and saline MO biocoagulants were performed by the morphological analysis via SEM, zeta potential and quantification of soluble proteins. It was observed that the coagulation / flocculation / sedimentation process using the lyophilized OM biocoagulant under optimum conditions demonstrated better shelf-life performance in a one-year storage period when compared to the freshly-used fresh OM biocoagulant after the first and second day of preparation. For the comparative study carried out between the biocoagulant of MO and the inorganic aluminum sulphate coagulant when applied in wastewater from industrial textile laundry, the effects of pH and the different concentrations of coagulants were evaluated using a RCCD and the variables responses were evaluated simultaneously by the desirability function. For the treatment of coagulation/flocculation the best results obtained of color removal and turbidity with biocoagulant of MO were (63.98% and 66.29 at pH 4.02, respectively) whereas for aluminum sulphate the highest percentages obtained were 82.09% for color and 88.24% for turbidity at pH 10. The optimum values of pH and MO obtained with the model were 3 and 3000 mg L-1 and for aluminum sulfate 10 and 2750 mg L-1, in which a percentage of color removal of 67.13% and turbidity of 91.98% were obtained with the biocoagulant of MO and 81.45% and 92%, respectively, for the inorganic aluminum sulfate coagulant . Thus, it is possible to conclude that there is stability in the coagulation potential efficiency over the useful life time and when applied in wastewater from the industrial process of textile washer and compared to the use of aluminum sulfate coagulant, the values obtained of the percentages of removal are satisfactory, making it possible to use lyophilized MO biocoagulant. Thus, it is possible to conclude that there is stability in the coagulation over the useful life time and when applied in waste water from the industrial process of textile washer and compared to the use of the aluminum sulfate coagulant, the values obtained of the percentages of removal are satisfactory providing the use of lyophilized MO biocoagulant.